Functionalized selenium nanoparticles ameliorated acetaminophen-induced hepatotoxicity through synergistically triggering PKCδ/Nrf2 signaling pathway and inhibiting CYP 2E1 - Si Zou; Yetao Gong; Xiujie Li; Yanbin Wu; Jinzhong Wu; Jianguo Wu; Ka-Hing Wong (Food Science and Human Wellness)
Selenium nanoparticles (SeNPs) have been demonstrated potential for use in diseases associated with oxidative stress. Functionalized SeNPs with lower toxicity and higher biocompatibility could bring better therapeutic activity and clinical application value. Herein, this work was conducted to investigate the protective effect of Pleurotus tuber-regium polysaccharide-protein complex funtionnalized SeNPs (PTR-SeNPs) against acetaminophen (APAP)-induced oxidative injure in HepG2 cells and C57BL/6J mouse liver. Further elucidation of the underlying molecular mechanism, in particular their modulation of Nrf2 signaling pathway was also performed. The results showed that PTR-SeNPs could significantly ameliorate APAP-induced oxidative injury as evidenced by a range of biochemical analysis, histopathological examination and immunoblotting study. PTR-SeNPs could hosphorylate and activate PKCδ, depress Keap1, and increase nuclear accumulation of Nrf2, resulting in upregulation of GCLC, GCLM, HO-1 and NQO-1 expression. Besides, PTR-SeNPs suppressed the biotransformation of APAP to generate intracellular ROS through CYP 2E1 inhibition, restoring the mitochondrial morphology. Furthermore, the protective effect of PTR-SeNPs against APAP induced hepatotoxicity was weakened as Nrf2 was depleted in vivo, indicating the pivotal role of Nrf2 signaling pathway in PTR-SeNPs mediated hepatoprotective efficacy. Being a potential hepatic protectant, PTR-SeNPs could serve as a new source of selenium supplement for health-promoting and biomedical applications.